Seni Kriya Sulaman Tangan Tradisional dan Pengrajin Perempuan Nagari Koto Gadang dalam Dimensi Ekonomi, Sosial dan Budaya - Purwo Prihatin (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This research was motivated by the existence of Minangkabau women's crafts and craftsmen, especially in Koto Gadang who have skills in the field of traditional hand embroidery. This study aims to find out the traditional hand-embroidered craft art of women in nagari Koto Gadang as cultural actors who carry out processes in social activities and craft arts. The research method uses a type of qualitative research, data collection through written sources and literature studies, documentation of cultural artifacts, so that this study can be produced and concluded that the traditional embroidery craft art of Koto Gadang is the embodiment of the expression of aesthetic taste in the form of functional objects and aesthetic objects which in their creation requires ability, experience, and technical skills such as embroidery, terawang, kapalo samek, and suji cair. Traditional embroidery crafts apply ornamental motifs, both flora, fauna and other objects based on nature, become teachers. The traditional embroidery craft art in Koto Gadang as a social product has an impact on the dimension of women's lives in Koto Gadang. The presence of Koto Gadang women and the art of embroidery crafts has become a manifestation of minangkabau women's activities that have produced cultural identity and positively impacted the actors and supporters both the social dimension and the economic dimension.